Tinjauan Hukum Internasional Terhadap Perdagangan Manusia di Asia Tenggara - Rahmadhani, Larasati; Permatasari, Angelina Dewi (Media Hukum Indonesia (MHI), 2025)
Human trafficking is one of the most complex forms of human rights violations, transcending national borders, with Southeast Asia being one of the most vulnerable regions to this crime. This study aims to examine the international legal framework governing human trafficking and to explore the challenges faced by Southeast Asian countries in its implementation. Using a qualitative research method with a normative juridical approach, this study analyzes international legal instruments such as the Palermo Protocol and the United Nations Convention against Transnational Organized Crime, as well as regional and national legal documents. Data collection techniques include case law analysis and legal literature review to understand the practical application of these laws. The findings indicate that although most countries in the region have ratified various international instruments, implementation at the national level remains hindered by weak law enforcement, lack of regulatory harmonization, and suboptimal regional coordination. This study recommends strengthening institutional capacity, updating national legislation in accordance with international standards, and enhancing inter-state cooperation to combat human trafficking more effectively.